2024
DOI: 10.5132/eec.2017.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of silica nanoparticles on Allium cepa

Abstract: Nanotechnology is rapidly expanding, and several new nanoparticle products with improved performance have been developed. The environmental fate and toxicity of nanoparticles (NP) is poorly understood and should be studied to enable the safe use of this technology. This study aims to investigate genotoxic and phytotoxic impacts of silica nanoparticles (SiNP) using root tip cells of Allium cepa as an indicator system. A. cepa root tip cells were exposed to different concentrations (1.82 to 0.54 g L-1 ; dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
2
8
2
Order By: Relevance
“…However, the mitotic index at the highest n-TiO 2 concentration (75 mg/L) was significantly lower than that at the lowest n-SiO 2 concentration (25 mg/L) ( Table 1). The positive effect of n-SiO 2 at the low concentration is in contrast to the previous results on L. culinaris at the same concentrations [24] and A. cepa at concentrations of 540-1820 mg/L [51]. Although n-TiO 2 may [7,20,32].…”
Section: Mitotic Index and Mitotic Phasecontrasting
confidence: 83%
See 3 more Smart Citations
“…However, the mitotic index at the highest n-TiO 2 concentration (75 mg/L) was significantly lower than that at the lowest n-SiO 2 concentration (25 mg/L) ( Table 1). The positive effect of n-SiO 2 at the low concentration is in contrast to the previous results on L. culinaris at the same concentrations [24] and A. cepa at concentrations of 540-1820 mg/L [51]. Although n-TiO 2 may [7,20,32].…”
Section: Mitotic Index and Mitotic Phasecontrasting
confidence: 83%
“…For n-SiO 2 , similar results were obtained at the concentrations of 90 and 180 mg/L on V. faba [42] and at even higher concentrations (400-4000 mg/L) on Arabidopsis thaliana [31]. On the other hand, n-SiO 2 decreased the germination percentage of A. cepa at 540, 810 and 1820 mg/L [51] and L. culinaris by increasing the concentration up to 300 mg/L [24]. Similar to our result, n-TiO 2 treatments did not influence the seed germination of Triticum aestivum (wheat) [18], Hordeum vulgare (barley) [32] and various plant species even at high concentrations (Table S3).…”
Section: Effects Of N-sio 2 and N-tio 2 On Germination And Plant Growthsupporting
confidence: 75%
See 2 more Smart Citations
“…Previous works showed that the toxicity from the silica nanotubes increases with the increase of microalgae cell diameter [48]. The other research described an increase in the phytotoxic action for silica NPs with increase of particle size [49]. For C. muelleri and P. purpureum, which are the algae species having smaller cell sizes, both types of silica nanotubes demonstrated a comparable level of toxicity, though the minor predominance could be seen for the sample SNT-1 (Table 3, Figure 1) with smaller diameter of nanotubes but a more developed surface area.…”
Section: Silica Nanotubesmentioning
confidence: 98%